Revision of the Australian endemic ant genera Pseudonotoncus and Teratomyrmex (Hymenoptera: Formicidae: Formicinae) - Shattuck, S. O.; O’reilly, A. J. (Zootaxa, 2013)
The Australian endemic formicine ant genera Pseudonotoncus and Teratomyrmex are revised and their distributions and biologies reviewed. Both genera are limited to forested areas along the east coast of Australia. Pseudonotoncus is known from two species, P. eurysikos (new species) and P. hirsutus (= P. turneri, new synonym), while Teratomyrmex is known from three species, T. greavesi, T. substrictus (new species) and T. tinae (new species). Distribution modelling was used to examine habitat preferences within the Pseudonotoncus species.